2020
DOI: 10.3354/meps13274
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally specific responses to wind patterns and ocean productivity facilitate the longest animal migration on Earth

Abstract: Migratory strategies of animals are broadly defined by species’ eco-evolutionary dynamics, while behavioural plasticity according to the immediate environmental conditions en route is crucial for energy efficiency and survival. The Arctic tern Sterna paradisaea is known for its remarkable migration capacity, as it performs the longest migration known by any animal. Yet, little is known about the ecology of this record-breaking journey. Here, we tested how individual migration strategies of Arctic terns are ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…5 & S4). Similar results have been found in previous studies on the same species (Hatch et al 2010, Frederiksen et al 2012, Mosbech et al 2012, Fayet et al 2016, Merkel et al 2021 and in many other seabird species such as Arctic terns, long-tailed skuas, sooty shearwaters and wandering albatrosses (Shaffer et al 2006, Weimerskirch et al 2015, van Bemmelen et al 2017, Hromádková et al 2020. Seabird migration patterns therefore did not match the dispersive migration definition (Newton 2007).…”
Section: Broad-scale Migratory Movementssupporting
confidence: 84%
See 1 more Smart Citation
“…5 & S4). Similar results have been found in previous studies on the same species (Hatch et al 2010, Frederiksen et al 2012, Mosbech et al 2012, Fayet et al 2016, Merkel et al 2021 and in many other seabird species such as Arctic terns, long-tailed skuas, sooty shearwaters and wandering albatrosses (Shaffer et al 2006, Weimerskirch et al 2015, van Bemmelen et al 2017, Hromádková et al 2020. Seabird migration patterns therefore did not match the dispersive migration definition (Newton 2007).…”
Section: Broad-scale Migratory Movementssupporting
confidence: 84%
“…In particular, birds reaching the North-West Atlantic travelled along South-East Greenland in the autumn and came back by crossing the Atlantic Ocean south from Iceland. These routes are likely to follow wind and current regimes, which may reduce the energetic costs of migration and ultimately shape the geographic distribution of birds in the non-breeding season (Adams & Flora 2010, Hromádková et al 2020. The fact that several species share the same migration routes also increases the need to consider protection of 'migratory corridors' as a broader ecosystem unit rather than species-specific routes and areas.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…This pattern differs from other seabirds that follow similar migratory paths. For instance, Arctic terns migrate 1.5 times faster in spring than in fall while covering similar distances (Egevang et al 2010, Hromádková et al 2020. The slower travel speed in spring and the higher number of daily immersions (more time in contact with saltwater) compared to fall provide evidence that jaegers adopt some sort of flyand-forage migration strategy in spring (Strandberg & Alerstam 2007).…”
Section: Travel Speed and Phenologymentioning
confidence: 99%
“…In particular, successful animal migration should depend on how individuals adjust behaviors between and within seasons [ 2 ], because changing behaviors as weather and ecological variables vary along the route can reduce the costs of migration [ 3 , 4 ] and even lead to the avoidance of hazardous weather events to ensure survival [ 5 ]. Although mechanistic explanations of decision-making remain unclear [ 6 ], research on birds has shown that individuals can select favorable winds [ 5 , 7 , 8 ], weather [ 9 , 10 ], flight altitudes [ 11 ], routes [ 12 , 13 ] and stopover frequency [ 14 ] and sites [ 15 , 16 ]. Between years, changes in migratory timing for several species have also been documented [e.g.…”
Section: Introductionmentioning
confidence: 99%